Cement consolidation injections in fine soils - Ramírez Niño, Carlos Andres; Pesca Gamba, Néstor Andrés; Ramírez, Óscar Hernan (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The process of soil improvement with this technique was developed by choosing a site where fine soils are present, to proceed with a geotechnical exploration and characterization, determining the physical and mechanical properties of the study soil. With the results obtained, the next step corresponds to the adaptation of the injection equipment to start the consolidation injections. The injections were made in the same holes of the exploration with a water-cement slurry, determining a range of pressures. After the injections were made, a new exploration was made to determine, by comparing the parameters, the change in the physical and mechanical properties of the soil and thus observe the usefulness of the improvement process.